2021
DOI: 10.1002/jbt.22901
|View full text |Cite
|
Sign up to set email alerts
|

Betulinic acid abates N‐nitrosodimethylamine‐induced changes in lipid metabolism, oxidative stress, and inflammation in the liver and kidney of Wistar rats

Abstract: N-nitrosamines have been linked with cancer in humans due to their presence in drinking water and diets. This study evaluated the role of betulinic acid (BA) in abating oxidative stress, inflammation, and hyperlipidemia in rats treated with N-nitrosodimethylamine (NDMA). Twenty-four male rats were assigned into four equal groups. Group I served as the control, Group II received BA (25 mg/kg), Group III received NDMA (5 mg/kg) and, Group IV received BA (25 mg/kg) and NDMA (5 mg/kg). Results showed that the admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Thus, it is crucial to study the effects of exposure to nitrosamines higher than the guideline value on human health. Some previous studies have confirmed that nitrosamines could cause inflammatory responses in the liver and kidney of rats (Adeleke & Adaramoye, 2021; Balaraman et al, 2021). Mixed exposure to nitrosamines and LPS in tobacco could lead to the inflammatory response in bronchial epithelial cells (Liu et al, 2021).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Thus, it is crucial to study the effects of exposure to nitrosamines higher than the guideline value on human health. Some previous studies have confirmed that nitrosamines could cause inflammatory responses in the liver and kidney of rats (Adeleke & Adaramoye, 2021; Balaraman et al, 2021). Mixed exposure to nitrosamines and LPS in tobacco could lead to the inflammatory response in bronchial epithelial cells (Liu et al, 2021).…”
Section: Discussionmentioning
confidence: 81%
“…Thus, it is crucial to study the effects of exposure to nitrosamines higher than the guideline value on human health. Some previous studies have confirmed that nitrosamines could cause inflammatory responses in the liver and of rats (Adeleke & Adaramoye, 2021;Balaraman et al, 2021).…”
Section: Nlrp3 Inflammasome Activation Mediated the Pyroptosis Of Het...mentioning
confidence: 80%
“…38 [25,55] 29 [19,42] 47 [32,68] 28 [19,41] 47 [32,67] 37 [25,53] 38 [25, 49 [29,81] 42 [23,72] 53 [32,87] 41 [22,70] 56 [34,92] 47 [28,75] 51 [29,88] Tea (g/d)…”
Section: Associations Between Plant-and Vegetable-sourced Nitrate And...mentioning
confidence: 99%
“…Indeed, participants with the highest intakes of additive-permitted meat sourced nitrate and nitrite are expected to live, on average, 4 months less than those with the lowest intakes. This may be due to an increase in inflammation and oxidative stress seen with exposure to NOCs [41,42]. While the literature on the effect of NOCs confounding-namely by sociodemographic, dietary, water pollutant, and air pollutant confounders-cannot be ruled out.…”
Section: Exposure Intakes Are Presented As Median [Iqr]mentioning
confidence: 99%
“…Betulinic acid (BA) is a lupane-type pentaloidal triterpenoid that is widely distributed in the bark, leaves, flowers, and fruits of plants, such as birch, rosemary, perilla, loquat, clove, coffee, jujube, and apple [ 1 ]. Previous studies have shown that BA exerts various biological activities, such as antitumor, liver protection, anti-inflammatory, antihuman immunodeficiency virus, antioxidative stress, antiatherogenic, and antiobesity [ 2 ]. Among them, the antitumor activity of BA has been extensively studied, for example, in liver cancer [ 3 ].…”
Section: Introductionmentioning
confidence: 99%